FeF3 as a green catalyst for the synthesis of dihydropyrimidines via Biginelli reaction - Krishna, Thalishetti; Laxminarayana, Eppakayala; Kalita, Dipak (European Journal of Chemistry, 2020)
A facile and highly efficient FeF3-catalyzed method has been developed for the direct synthesis of functionalized dihydropyrimidines from readily available starting materials via Biginelli reaction. These reactions proceed at low-catalyst loadings with high functional group tolerance under mild conditions. This method provides efficient reusability of the catalyst and good to excellent yields of the products, making the protocol more attractive, economical, and environmentally benign. FeF3 is an attractive catalyst for the Biginelli reaction because of its high acidity, thermal stability and water tolerance.